IMPROVING THE SYSTEM OF SOCIAL AND PEDAGOGICAL SUPPORT FOR PRIMARY SCHOOL-AGE CHILDREN FROM DYSFUNCTIONAL FAMILIES - Nurullayeva, Sarvinoz Murodovna; Kurbaniyazova, Zamira Kalbaevna (SCIENCE and SOCIETY, 2026)
This article is devoted to improving the system of socio-pedagogical support for primary school students from dysfunctional families. It analyzes the impact of the family environment on children’s development, the current state of existing support mechanisms, and international experience. Based on the study, practical and methodological recommendations for the development of the system are proposed. The necessity of strengthening cooperation between the family, school, and social institutions, early identification, and the implementation of individualized support is substantiated. The findings provide an important basis for scientific and practical activities.
Keywords: dysfunctional family; socio-pedagogical support; primary school age; child development; education system; individualized support; family-school cooperation